JURIDICAL STUDIES OF THE LEGAL STATUS OF DIGITAL RUPIAH IN THE CONTEXT OF MODERNIZING FINANCIAL MARKET INFRASTRUCTURE - Bakhtiyar, Annisa Carolina; Rosadi, Sinta Dewi; Handayani, Tri (Jurnal Poros Hukum Padjadjaran, 2023)
The rise of exchange rates other than the official state currency in the digital world raises its own problems. The development of the digital economy that is currently developing is supported by digital economic infrastructure, one of which is the official state medium of exchange. Therefore, this is a demand for the public's need for official state exchange instruments that can apply in the digital world. This was then answered by Bank Indonesia through the concept of Digital Rupiah and its derivatives in various Bank Indonesia Regulations. However, there are problems regarding the Digital Rupiah policy and the implementation of secure use of the Digital Rupiah sistem. This research was conducted using a normative juridical method, and the writing stage was carried out through a literature search which was carried out by examining secondary data including primary legal materials, literature, articles, opinions and teachings of experts and their implementation in laws and regulations. Based on the discussion, it can be concluded that policies related to Digital Rupiah as a modernization of financial market infrastructure are still contained in various regulations, including Law Number 4 of 2023, Bank Indonesia Regulation Number 23/11/PBI/2021, and Bank Indonesia Regulation Number 23/10 /PBI/2021. Digital Rupiah security arrangements in Indonesia refer to Bank for International Settlements (BIS) guidelines and include secure technology infrastructure, cloud-based cybersecurity services, risk management and compliance sistems, as well as application and infrastructure security integration through DevSecOps. Reliability certificates are regulated in Government Regulation Number 71 of 2019.